Состояние печени и липидного обмена при экспериментальном кишечном дисбиозе у крыс - Ткачук, В.В. (Актуальні проблеми транспортної медицини, 2015)
При кишечном дисбиозе, который вызывали у крыс с помощью линкомицина, в печени развивался дисбиоз и воспалительно-дистрофический процесс. Вследствие этого повышался уровень триглицеридов в печени (стеатоз) и в сыворотке крови (гиперлипидемия). Аналогичные изменения происходили и при оральных аппликациях геля с липополисахаридом. За умов кишкового дисбіозу, який викликали у щурів за допомогою лінкоміцину, в печінці розвивався дисбіоз та запально-дистрофічний процес. Як наслюдок, підвищувався рівень тригліцеридів в печінці (стеатоз) і в сироватці крові (гіперліпідемія). Аналогічні зміни відбувалися і після оральних аплікацій гелю з ліпополісахаридом. Aim: To determine the effect of dysbiosis and lipopolysaccharide on the liver condition and the lipid metabolism. Materials and Methods: Intestinal dysbiosis in rats was reproduced using lincomycin. Lipopolysaccharide (LPS) from E. coli was used for the oral administration at the dose 200 mg/kg. The degree of dysbiosis was evaluated by the ratio of the relative activities of urease and lysozyme. The liver condition was determined by the level of inflammation markers in the liver (MDA and elastase) and the ALT activity in the blood serum. The lipid metabolism was evaluated by triglycerides and cholesterol in the liver and the blood serum. Results: It was found the development of dysbiosis in the liver, and inflammation both at intestinal dysbiosis and at the exposure to LPS. The triglycerides‘ level increased in the liver and in the blood serum of rats having dysbiosis and treated with LPS. The cholesterol level did not change. Conclusions: Intestinal dysbiosis causes the development of steatohepatitis by the exposure to LPS.